Transforming local knowledge into lifestyle entrepreneur’s innovativeness: exploring the linear and quadratic relationships - Dias, Á. (2021)
Tourism Lifestyle Entrepreneurs (TLEs) play an essential role in the innovation and competitiveness of tourist destinations. However, little attention has been paid to how these entrepreneurs manage local knowledge and turn it into innovation. This research examines how place attachment, community-centered strategy, and knowledge assimilation influence lifestyle entrepreneur’s innovativeness. A mixed methodology was applied with an online survey of 511 TLEs being conducted first, followed by a qualitative research where 24 additional TLEs were in depth-interviewed. Empirical evidence shows that, while place attachment and community-centered strategy have a positive linear relationship with lifestyle entrepreneur innovativeness, knowledge assimilation has a U-shaped relationship. Based on this U-shaped relationship, three types of TLEs were identified according to their capacity to transform assimilated knowledge into innovation, namely, opportunity seekers, professionals and laggards. The theoretical and practical implications are essential for the management of a tourism destination.